Social Media Ethics in Building a Healthy Digital Space - Irawan, Deni; Hidayatullah, Ryan (Indonesian Journal of Research and Service Studies, 2024)
The development of social media has created both opportunities and challenges in building a healthy digital space, particularly due to the increasing spread of disinformation, hate speech, privacy violations, and low awareness of digital ethics. This study aims to analyze the role of social media ethics in building a healthy digital space through a qualitative approach using a literature review method. Data were obtained from reputable scientific articles, academic books, and relevant policy documents and analyzed using qualitative content analysis through a thematic synthesis process. The results reveal four main themes: social media ethics as a foundation for digital citizenship, instruments for preventing disinformation and hate speech, strengthening through digital literacy and education, and ethical challenges in the era of artificial intelligence. This study concludes that social media ethics is a fundamental factor in creating a safe, inclusive, and sustainable digital space through the synergy of digital literacy, social responsibility, education, and digital governance.